2018
DOI: 10.2139/ssrn.3227972
|View full text |Cite
|
Sign up to set email alerts
|

Trade Linkages and Firm Value: Evidence from the 2018 US-China 'Trade War'

Abstract: On March 22, 2018, Trump proposed to impose tariffs on up to $50 billion of Chinese imports leading to a significant concern over the "Trade War" between the US and China. We evaluate the market responses to this event for firms in both countries, depending on their direct and indirect exposures to US-China trade. US firms that are more dependent on exports to and imports from China have lower stock and bond returns but higher default risks in the short time window around the announcement date. We also find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 61 publications
2
100
0
Order By: Relevance
“…In addition, the GTAP model does not incorporate the financial sector and hence effects are limited to the real economy. For instance, Huang, Lin, Liu, and Tang () found that prior to the trade war, US firms trading heavily with China tend to have poorer financial market performance such as lower bond and stock returns.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the GTAP model does not incorporate the financial sector and hence effects are limited to the real economy. For instance, Huang, Lin, Liu, and Tang () found that prior to the trade war, US firms trading heavily with China tend to have poorer financial market performance such as lower bond and stock returns.…”
Section: Resultsmentioning
confidence: 99%
“…Our results have so far focused on market-wide effects, but as Huang et al (2018) suggest, impacts may be heterogenous across sectors. Industries that are more exposed to trade, either through the input or output market, should be more exposed.…”
Section: Sector-level Resultsmentioning
confidence: 95%
“…Crowley et al (2018), using Chinese customs data from 2000 and 2009, find that Chinese firms are less likely to enter new foreign markets and more likely to exit from established foreign markets when their products are subject to increased trade uncertainty. Huang et al (2018) assess the stock market responses of both U.S. and Chinese firms to a single protectionist event on March 22, 2018, showing how impact can change, depending on the extent of firms' exposure to U.S.-China trade through input-output linkages. Crowley et al (2019) find that daily stock market returns of larger, more export-oriented Chinese solar panel producers decline after the announcements of European import restrictions against Chinese solar panel products.…”
Section: Introductionmentioning
confidence: 99%
“…Almost every study analyzed that the intention of US behind tariff hike was to close the wide trade deficit of US-China. US government believed that it will help in reducing competition from Chinese firms and due to weaken competitiveness, Chinese government will be forced to implement favorable policies (Huang et al, 2018). Whereas, the decision equally hurts the US economy as well.…”
Section: Estimated Impact On Us China and World Economymentioning
confidence: 99%